Sistem Informasi Penerimaan Siswa Baru Di Sekolah Menengah Atas - Melda, M; Suppa, Rinto; Paembonan, Solmin (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2021)
This study aims to design an information system for new student admissions at SMA Negeri 4 Luwu. The research method used is the system development method with the waterfall model. Data collection techniques using data documentation methods, interviews and observations. This new admissions information system in its design uses the UML (Unified Modeling Language) development method which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams. Database logic design using My SQL and system interface. The software used in designing and implementing or supporting the system uses XAMPP as a web server, PhpMySQL as a database, HTML as a framework or format for a web, PHP as a language used on the server side, black box as a system test and a browser as a display media. The new student admission information system at SMA Negeri 4 Luwu includes new student registration, registration information, announcements, managing registration information and approving registration. The information system has been tested (test case) in order to obtain an information system that runs well